Pemodelan dan Prediksi Pola Musiman Menggunakan Holt-Winters - Pangruruk, Thesya Atarezcha; Mangiri, Nalto Batty; Rombeallo, Esra; Nurmayanti, Wiwit Pura (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2025)
Samarinda City, with its tropical climate, experiences significant variations in rainfall throughout the year. This instability has the potential to cause impacts such as flooding, disruptions in the agricultural sector, and damage to infrastructure. This study aims to analyze and forecast the seasonal rainfall patterns in Samarinda City by applying the Holt Winters Exponential Smoothing method based on a multiplicative model. Monthly rainfall data were analyzed to identify stationarity properties in both mean and variance. The results indicate that the data are stationary in the mean but not in the variance, thus justifying the use of the Holt-Winters Multiplicative Exponential Smoothing model. Parameter estimation yielded alpha , beta , and gamma values of 1 each, with a MAPE of 50%, indicating a moderate level of accuracy. Despite the relatively high error rate, the model remains effective in illustrating seasonal patterns, which can be useful for preliminary water resource management planning in the region